Design and Experimental Investigation of Calcium Looping Process for 3‐kWth and 1.9‐MWth Facilities. Issue 9 (2nd August 2013) - Chang, M.‐H.; Huang, C.‐M.; Liu, W.‐H.; Chen, W.‐C.; Cheng, J.‐Y.; Chen, W.; Wen, T.‐W.; Ouyang, S.; Shen, C.‐H.; Hsu, H.‐W.; Epple, Bernd
Abstract The calcium looping CO2 capture process using calcium oxide as a regenerable solid sorbent has been under development at the Industrial Technology Research Institute (ITRI) of Taiwan for several years. The 3‐kWth test facility built at ITRI is mainly composed of a fluidized‐bed carbonator and a rotary kiln calciner. The calcination efficiency, the CO2 capture efficiency, and operating stability were investigated. In addition, a cold model test facility has been constructed and a 1.9‐MWth pilot plant designed by ITRI is currently being erected. The combination of calcium looping and cement manufacturing process reduces the cost of adsorbent and calcination energy consumption.